PECULIARITIES OF BORROWING OF ECONOMIC TERMS AND THEIR ASSIMILATION - Barno Abdullaeva, Shin, Sung-Jae , Abduvalieva Dilsora Shamuratov Rustam Artikbaeva Sayyora (International Journal of Advanced Science and Technology, 2020)
By economic terms, we understand the acts of speech in the economic sphere, as well as oral and written texts or their fragments reflecting the realities of the economic world which are created by professionals, non-specialists and journalists. In this article described peculiarities of borrowing of economic terms and their assimilation process by language users.